2011
DOI: 10.1111/j.1467-9299.2011.02004.x
|View full text |Cite
|
Sign up to set email alerts
|

eHEALTH IN THE PUBLIC SECTOR: AN EMPIRICAL ANALYSIS OF THE ACCEPTANCE OF GERMANY'S ELECTRONIC HEALTH CARD

Abstract: Given the increasing importance of eHealth as an integral part of eGovernment, this contribution concentrates on the issue of acceptance regarding the introduction of the German electronic health card (eHC). A brief introduction highlights the relevance of the subject and the differing acceptance rates of patients and service providers, i.e. physicians. Based on both the technology acceptance model and the relevant literature, important factors influencing the attitude towards and the potential use of the eHC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 30 publications
(56 reference statements)
2
8
0
Order By: Relevance
“…Needless to say, the development of e-government and supporting management information systems, strengthened the timing, accuracy, and targeting of the delivery of public services in all areas of the local government. This corroborates with findings in previous studies on e-government development (Chen, Gibson, & Geiselhart, 2006;Dawes, 2008) on the impact that egovernment development and deployment on enhancing the quality and quantity of services that are provided as well as access of services to users, regardless of geographical locations (Wirtz, Mory, & Ullrich, 2012).…”
Section: The Institutional Approach Analysis Of Electronic Governmentsupporting
confidence: 91%
“…Needless to say, the development of e-government and supporting management information systems, strengthened the timing, accuracy, and targeting of the delivery of public services in all areas of the local government. This corroborates with findings in previous studies on e-government development (Chen, Gibson, & Geiselhart, 2006;Dawes, 2008) on the impact that egovernment development and deployment on enhancing the quality and quantity of services that are provided as well as access of services to users, regardless of geographical locations (Wirtz, Mory, & Ullrich, 2012).…”
Section: The Institutional Approach Analysis Of Electronic Governmentsupporting
confidence: 91%
“…Other studies also identified social influence as the determinant of the acceptance of eHealth [35]. Yet other studies found that social influence had a significant impact on perceived usefulness [36]. Therefore, the following hypotheses are developed.…”
Section: H2mentioning
confidence: 96%
“…TAM was proposed by Davis (1989) to study the role of human behavior attributes in the acceptance of an information system. TAM is an adaptation of a psychological theory, Escobar-Rodriguez and Romero-Alonso (2013) 118 Medical staff E-health system TAM Glegg et al (2013) 42 Medical staff E-health tool DTPB Guo et al (2013) 204 Public E-health system TAM Hendrikx et al (2013) 68 Patients E-health system TAM Huang (2013) 369 Public E-health tool TAM (continued ) Kuo et al (2013) 665 Medical staff E-health tool TAM Liu et al (2013) 50 Patients E-health tool TAM Martínez-Caro et al (2013) 256 Patients E-health system TAM Monthuy- Blanc et al (2013) 205 Medical staff E-health tool TAM Noblin et al (2013) 560 Patients E-health tool TAM Nuq and Aubert (2013) 329 Medical staff E-health system TAM Sun et al (2013) 204 Public E-health system TAM, TPB Tsai et al (2013) 101 Public E-health tool TAM Aldosari (2012) 89 Medical staff E-health system TAM Bhagya Lakshmi and Rajaram (2012) 465 Medical staff E-health system TAM Chen and Hsiao (2012) 81 Medical staff E-health system TAM Dünnebeil et al (2012) 117 Medical staff E-health system TAM Escobar- Rodríguez et al (2012) 209 Medical staff E-health tool TAM Hung and Jen (2012) 170 Public E-health system TAM 224 Medical staff E-health tool DTPB Ketikidis et al (2012) 133 Medical staff E-health system TAM Kim and Park (2012) 728 Public E-health system TAM 449 Patients E-health system TAM Kowalczyk (2012) 110 Medical staff E-health tool TAM2 Lu et al (2012) 277 Medical staff E-health system TAM Maass and Varshney (2012) 51 Public E-health system TAM, TPB Wirtz et al (2012) 502 Medical Staff E-health tool TAM Xue et al (2012) 700 Public E-health tool TAM Cudmore et al (2011) 192 Public E-health system TAM Dyball et al (2011) 48 Medical staff E-health system TAM Egea and González (2011) 254 Medical staff ...…”
Section: Tam and Related Theoriesmentioning
confidence: 99%